Aortic stenosis: correlation of prenatal echocardiography to postmortem histology. (14th October 2021) - Zwanenburg, F; Van Munsteren, J C; Wisse, L J; De Ruiter, M C; Haak, M C; Jongbloed, M R M
Abstract: Background: Foetal aortic stenosis (AS) is a challenging congenital heart disease considering its potential to progress during the course of pregnancy. Especially at midgestation, it remains extremely difficult to distinguish the cases that end up biventricular from the cases that will develop into an hypoplastic left heart syndrome. Purpose: To test the hypothesis that the degree of myocardial maturation is a possible predictor of biventricular outcome, we present 4 cases of foetal AS with a varying degree of severity and uniquely correlate differences in myocardial function based on prenatal echocardiography to their post-mortem histopathologic maturation. Methods: We selected 4 cases with midgestational AS from our tertiary foetal cardiology service between 2018–2020. Speckle tracking recordings of the cardiac four-chamber view were performed during routine foetal echocardiography to quantify myocardial wall motion as a marker for myocardial function. Three cases decided to terminate the pregnancy and donated the cardiac specimen. Immunohistochemical labelling (ICH) against key markers for myocardial maturation (troponin-I, N-cadherin, connexin-43, MLC2A, MLC2V and α-SMA) and fibrosis (Sirius Red) were compared with 2 normal foetal cardiac specimens. Results: Two cases with critical AS presented extremely decreased global and segmental longitudinal strain (GLS and SLS) values (GLS −2% and −0.9%) in the left ventricle (LV), indicating an impaired myocardial wall deformation. Post-mortem ICH showed overt endocardial fibro-elastosis (EFE) and pathological fibrosis patterns in the subendocardial layer which was remarkably spatially correlated to the EFE. The cardiomyocytes were disorganised with reduced expression of troponin-I and disturbed expression of connexin-43. The remaining 2 cases had normal LV appearance on foetal echocardiography, showing a mild reduction in left ventricular GLS and SLS (GLS −11.8% and −14.2%). Post-mortem ICH of 1 of these cases showed mild EFE with a milder fibrosis pattern. Cardiomyocytes were less disorganised but also showed a disturbed expression of connexin-43. The 4th case continued the pregnancy and had a biventricular outcome. Conclusions: This is a unique case series showing that myocardial function correlates with high extent to histology. The degree of the reduction in myocardial function corresponded with the amount of pathological fibrosis patterns and disorganisation of the cardiomyocyte network. Myocardial wall motion on foetal echocardiography seems to hold promise as a possible marker for cardiac maturation. FUNDunding Acknowledgement: Type of funding sources: None.